Critical success factors for project management support information systems: SEBRAE/RN Case - Filgueira de Melo Moura, Tâmara Patrícia (REBRAE, 2016)
The current economic climate is driving the work of companies in the execution of projects that need to be managed and monitored periodically. Historically term goals, cost and quality are thermometers to measure success or failure of companies. For better project management, systems are needed that give support from the structure to the budget of each project, as well as its monitoring throughout the execution. The result of the components mentioned above reflect the overall results of the institution. Therefore, this study investigated through case study methodology, critical success factors for information systems that support project management in Sebrae/RN, and sought, through the project managers, to raise factors that influence decisions in search of improving the performance of the organization studied. Thus, a quantitative and qualitative research was applied. The results showed the critical success factors that hinder optimal performance of information systems from the structuring to the execution and monitoring of projects.